Analisis Aplikasi “ASN Memayu” Di Lingkungan Pemerintah Daerah Istimewa Yogyakarta - Taufan Taufan; Muh Ryan Rahmatul Hidayat (Post Graduate School of Government Science, 2023)
In the era of accelerating information, the Personnel Management Information System is very necessary to process employee administration from small to large scope in the context of the government environment. With increasing developments and needs resulting in many changes and regulations in the administrative process which is expected to be more efficient, effective and accurate in decision making in ASN management. The aim of this research is to analyze the ASN Memayu application within the Yogyakarta Special Region Provincial Government, and the supporting factors for implementing the digitization of the Yogyakarta Special Region Government's personnel information system. This research method is descriptive qualitative with a literature study approach. Data collection uses documentary data collection in the form of mass media news, journals and other documents according to the theme. Data analysts are used to reduce data, present data and draw conclusions. The research results explain that the application of information technology in managing personnel data in the Yogyakarta Special Region Provincial Government, especially through the ASN Memayu application, has experienced significant progress. The changes reflect a determination to improve efficiency, security and data accuracy. The development of the Memayu ASN application by the DIY Provincial Civil Service Agency is a strategic step in welcoming the era of digitalization, which is realized through rebranding of the civil service system and the use of digital technology. The progressive actions taken by BKD DIY form a strong basis for increasing effectiveness, efficiency and accountability in human resource management. The adoption of information technology in personnel management is not only a necessity, but also a real manifestation of commitment to achieving good governance and optimal public services through the comprehensive use of information technology.